Effect of growth factors and steroid hormones on heme oxygenase and cyclin D1 expression in primary astroglial cell cultures. Issue 3 (11th November 2014) - Bramanti, V.; Grasso, S.; Tomassoni, D.; Traini, E.; Raciti, G.; Viola, M.; Li Volti, G.; Campisi, A.; Amenta, F.; Avola, R.
Abstract : Astrocyte activity may be modulated by steroid hormones and GFs. This study investigates the interaction between glucocorticoids or estrogens and GFs on the expression of heme oxygenase‐1 (HO‐1) and cyclin D1 in astrocyte cultures at 14 days treated for 48 or 60 hr with dexamethasone (DEX) or 48 hr with 17β‐estradiol (E2 ) alone or with GFs added only in the last 12 or 24 hr. Twelve‐ or twenty‐four‐hour epidermal growth factor (EGF) treatment significantly enhanced HO‐1 expression in astrocyte cultures pretreated for 48 hr with DEX. A highly significant increase in HO‐1 expression was obtained after the last‐12‐hr EGF treatment in 48‐hr E2 ‐pretreated astrocyte cultures; this enhancement was particularly significant in 48‐hr E2 ‐pretreated cultures as well as in the last‐12‐hr insulin‐treated ones pretreated for 48 hr with E2. Sixty‐hour DEX‐alone pretreatment as well as the last‐12‐hr EGF treatment in 60‐hr DEX‐pretreated astrocyte cultures showed a significant increase of cyclin D1 expression. A significant decrease of cyclin D1 expression in the last‐12‐hr insulin‐like growth factor‐I (IGF‐1)‐treated cultures pretreated for 60 hr with DEX was observed. A highly significant enhancement in cyclin D1 expression in 14 days in vitro astrocyte cultures pretreated with E2 alone for 48 hr and treated in the last 12 hr with IGF‐1 in 48‐hr E2 ‐pretreated cultures was found. Finally, the data highlight an interactive dialogue between the growth factors and glucocorticoids or estrogens during the maturation of astroglial cells in culture that may control the HO‐1 and cyclin D1 expression as well as proliferating astroglial cells during the cell cycle. © 2014 Wiley Periodicals, Inc.